KARYA PASTORAL BAGI JANDA DI PAROKI ST. VINCENTIUS A PAULO KEDIRI - Oktavianus Antaris Jingga; Don Bosco Karnan Ardijanto (Lembaga Penelitian STKIP Widya Yuwana, 2023)
Widows have complex problems, in terms of caring of a child, ekonomic, psychology, sexual, and social. Responding to this problems, in Familiaris Consortio art. 71 the Church should be able to give anttention to the situation and condition of widows. The objectives of this research are: knowing the life situation of widows in St. Vincent parish Kediri, knowing the implementation of pastoral ministry for widows in St. Vincent de Paul parish Kediri and knowing the challenges in implementing pastoral ministry for widows in St. Vincent de Paul parish Kediri. This study uses a qualitative method with data collection technoques through interview with 8 respondents: 7 widows and 1 priest. This research resulted in several conclusions: 1) the life sitution of widows in St. Vincent de Paul parish Kediri has various life problems, both in terms of economic, psychology, spiritual, social, sexual, physical and mental, and parenting problem. 2) Pastoral ministry for widows in St. Vincent de Paul parish Kediri has been implemented. 3) The challenge in carrying out pastoral ministry for widows is getting negative perceptions from the people.